A Lyapunov Function and Global Stability for a Class of Predator-Prey Models - Xiaoqin Wang; Huihai Ma (Discrete Dynamics in Nature and Society)
We construct a new Lyapunov function for a class of predation models. Global stability of the positive equilibrium states of these systems can be established when the Lyapunov function is used.